Ethical approach to pharmacotherapy of comorbid states - Šendula-Jengić, Vesna (Array, 2009)
Ethics is an indispensable component of health care policy. Pharmacotherapy of comorbidity requires the use of a greater number of different drugs that have complex drug-drug interactions and drug-patient interactions which can cause various side-effects in the patient. The basic moral questions that justify the applied psychopharmacotherapy are the patient's welfare and preference, optimal relationship between risk and gain for the patient, and some include cost benefit as well